2023
DOI: 10.15587/1729-4061.2023.282061
|View full text |Cite
|
Sign up to set email alerts
|

Development of technology for the production of useful jelly candies from cucurbit crops on a natural basis

Alexandra Brindyukova,
Bipatyma Yerenova,
Laila Syzdykova
et al.

Abstract: The object of the study are the fruits of cucurbits crops, as well as confectionery products based on the fruits of watermelons and melons. The fruits of watermelons and melons are not processed on an industrial scale for a number of reasons: the lack of technological solutions for primary processing and preparation for processing, the instability of raw materials for processing. The pulp of watermelons must be processed within 5 hours under certain conditions; in the pulp of melons, changes in microbiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“… Elgamily, El-Sayed, El-Sayed, and Youssef (2023) discovered that jelly made from a natural prebiotic grape seed extract, combined with Lactobacillus rhamnobacteria, exhibited an anticariogenic effect. Brindyukova, Yerenova, Syzdykova, Abdiyeva, and Tlevlessova (2023) utilized watermelon and melon as raw materials to produce jelly, incorporating red monk fruit powder. The study demonstrated that this jelly has a shelf life of up to 30 days when stored at 6 °C and is resistant to mold.…”
Section: Non-starchy Jellymentioning
confidence: 99%
“… Elgamily, El-Sayed, El-Sayed, and Youssef (2023) discovered that jelly made from a natural prebiotic grape seed extract, combined with Lactobacillus rhamnobacteria, exhibited an anticariogenic effect. Brindyukova, Yerenova, Syzdykova, Abdiyeva, and Tlevlessova (2023) utilized watermelon and melon as raw materials to produce jelly, incorporating red monk fruit powder. The study demonstrated that this jelly has a shelf life of up to 30 days when stored at 6 °C and is resistant to mold.…”
Section: Non-starchy Jellymentioning
confidence: 99%